The Excess Burden of Indirect Taxation - Joseph, M. F. W. (Review of Economic Studies, 1939)
Journal Article The Excess Burden of Indirect Taxation Get access M. F. W. Joseph M. F. W. Joseph London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 6, Issue 3, June 1939, Pages 226–231, https://doi.org/10.2307/2967649 Published: 01 June 1939